INHIBITION OF CARBOHYDRATE HYDROLYSING ENZYMES BY METHANOLIC EXTRACT OF COUROUPITA GUIANENSIS LEAVES - GAURESH SOMANI; RAHUL CHAUDHARI; JAYANT SANCHETI; SADHANA SATHAYE (International Journal of Pharma and Bio Sciences, 2012)
The present study investigated the inhibitory effect of methanolic extract of Couroupita guianensis leaves (MCG) on carbohydrate hydrolysing enzymes and glucose uptake in isolated rat hemidiaphragm. Method: The effects of MCG at different concentrations (1.25-10mg) were carried out on carbohydrate hydrolysing enzymes namely porcine pancreatic α- amylase, rat intestinal α-glucosidase and sucrase. The effect of MCG on glucose utilisation was evaluated by estimating glucose uptake in isolated rat hemidiaphragm. Results: MCG showed significant dose dependent on inhibition of rat intestinal sucrase (IC50 = 2.38 mg/ml), rat intestinal maltase (IC50 = 2.5mg/ml) and porcine pancreatic α-amylase. (IC50 = 2.86 mg/ml). Furthermore, the glucose uptake in isolated rat hemidiaphragm was increased (P<0.001) by MCG when compared to the control group. Conclusion: These results suggest that MCG has signiï¬cant inhibitory activity on carbohydrate metabolizing enzymes and increases the peripheral utilization of glucose, indicating its probable therapeutic use as a potent antihyperglycemic agent.